Effectiveness of diet and exercise intervention programs on cardiovascular disease risk factors among postmenopausal Iranian women - Abedi, Parvin (2009)
Cardiovascular disease (CVD) is one of the major complications in menopausal women internationally. CVD, including heart diseases and stroke, are the leading causes of death, and is now a leading cause of death and disability in Iran. The aim of this study was to evaluate the effect of diet and exercise educational intervention on improving cardiovascular risk factors among postmenopausal Iranian women. This study started on June 2007 and was completed on May 2008. The study was carried out with participants recruited in a Health clinic in Ahvaz Iran. A total of 136 postmenopausal women were randomly assigned to four groups namely; exercise (38), diet (35), diet+ exercise (34) and control groups (29). The anthropometric, biochemical, health beliefs, physical activity and dietary intake of participants were measured at baseline and after six months. Over the six months intervention period, the three intervention groups received a multi-component educational consisting of one face-to-face education, three lecture discussion sessions and group counseling sessions (every week in the first month). They were also received three booklets about menopause, CVD, healthy diet and exercise with emphasis on components of Health Belief Model (HBM), monthly telephone reminders (each month after the first month) and individual counseling midway at the 3rd month. The control group received booklets only. Baseline and 6th month assessments were conducted by using the same questionnaires (interview-administered format). After six months intervention there was a significant positive change (P<0.05) in the physical activity level in the exercise group, perception of participants about seriousness, vulnerability, benefits, cues to action and barriers toward CVD in all three intervention groups. Also the dietary fiber, vitamin C and E intakes and distribution of participants who consumed ≥5 serving’s fruit and vegetable in the diet and diet+ exercise group increased significantly. The intervention improved some CVD risk factors significantly within groups in the following areas: Weight and BMI was reduced in the diet group, hip circumference decreased in the exercise and diet groups. The level of LDL decreased in the exercise in the group, VLDL and FBS decreased in the exercise and diet groups. The intake of protein increased in the diet + exercise group. Intake of monounsaturated fat increased in the exercise, diet and diet + exercise groups. Poly unsaturated fat and saturated fat intake decreased in the exercise group. The intake of vitamin A increased in the diet + exercise group and intake of calcium increased in the diet and diet + exercise groups. In conclusion the results of this study showed that six months of educational intervention of physical activity and diet could improve some risk factors of CVD in postmenopausal women. The diet and diet + exercise groups could reduce CVD risks more than the group that only exercised. Therefore, the implementation of healthy diets for postmenopausal women should be encouraged.